ISLAMIC EDUCATION STUDENT MANAGEMENT (CASE STUDY OF MA AL-MANSHUR) - SUPRIYADI, FAUSTA FIKA; BILQIS, ZAHRA NABILA; ASTUTI, WIWIN; PEMBANGUNAN, HELDY RAMADHAN PUTRA (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2024)
The world of education has entered the digital era marked by the development of information technology that can have a negative and positive impact on students, so the student field must be responsible for managing and producing students who are helpful to themselves and their environment. This research aims to get in-depth information on student management in Islamic educational institutions. This research was conducted using a qualitative descriptive approach method. The descriptive method is used because it follows the title and focus of the research, namely case studies. The results of this study show the scope of student management, the figures involved in student management, efforts to realize work programs, and obstacles faced by the Waka Student Affairs. ABSTRAKDunia pendidikan telah memasuki era digital yang ditandai dengan berkembangnya teknologi informasi yang dapat memberikan dampak negatif dan positif bagi peserta didik, sehingga bidang kesiswaan harus bertanggung jawab dalam mengelola dan menghasilkan peserta didik yang bermanfaat bagi dirinya dan lingkungannya. Penelitian ini bertujuan untuk mendapatkan informasi mendalam mengenai manajemen kesiswaan di lembaga pendidikan Islam. Penelitian ini dilakukan dengan menggunakan metode pendekatan deskriptif kualitatif. Metode deskriptif digunakan karena mengikuti judul dan fokus penelitian yaitu studi kasus. Hasil penelitian ini menunjukkan ruang lingkup manajemen kemahasiswaan, tokoh-tokoh yang terlibat dalam manajemen kemahasiswaan, upaya merealisasikan program kerja, dan kendala-kendala yang dihadapi Kemahasiswaan Waka.